DEVELOPMENT OF AN EXPERIMENTAL STAND AND METHODOLOGY FOR EXPERIMENTAL STUDIES OF A TWO-SUPPORT NON-CONTACT PNEUMATIC SPINDLE ON ADJUSTABLE CONICAL AEROSTATIC SUPPORTS - Breshev, Oleksii; Nosko, Pavlo; Bashta, Oleksandr; Bohdan, Svitlana; Bashta, Alla; Herasymova, Olha (Problems of Friction and Wear, 2026)
This article presents an experimental study of a high-speed pneumatic spindle with a two-point non-contact drive, equipped with adjustable conical aerostatic bearings. The design includes asymmetrical conical aerostatic bearings with adjustable clearances, intended to improve stability and load-bearing capacity during high-speed machining. The research follows a single-factor experiment methodology to verify a previously developed mathematical model. Key design improvements include an asymmetrical support system and a differential pair of screws for precisely adjusting the clearance. The article describes the experimental setup, measurement equipment, and the specific methodology for adjusting clearances based on total axial displacement. The results confirm the effectiveness of the proposed technical solutions and the adequacy of the mathematical model. This study lays the foundation for optimising non-contact drives by adjusting aerostatic support parameters to ensure reliable operation during high-speed material processing.